Histopathological spectrum of upper gastrointestinal lesions in a tertiary care centre - Kamath, Mridula; Shetty, Suchithra A; Khandige, Shreesha (Annals of Pathology and Laboratory Medicine, 2019)
Background: Gastrointestinal disorders are commonly encountered in clinical practice. Histopathologic examination of the endoscopic biopsies will help in definitive diagnosis and early therapeutic intervention. This study is done to know the various lesions presenting in our hospital. Materials and methods: This is a prospective study done in the Department of Pathology, Kanachur Institute of Medical Sciences between January 2018 to January 2019. 100 cases from esophagus up to the second part of duodenum were studied. The biopsies were sent to the histopathology lab in 10% buffered formalin. They were processed, sectioned and stained with H&E Results: of the 100 cases, 26 cases were from the esophagus, 66 from the stomach and 8 from duodenum. Of the 26 esophageal biopsies, 6 cases showed dysplastic changes, 4 had hyperplastic epithelium, 3 showed chronic inflammatory changes, 2 showed features of reflux esophagitis and 11 were diagnosed as Squamous cell carcinoma. Of the 66 gastric biopsies, majority were benign, commonest being chronic non specific gastritis. 8 cases were malignant and showed features of Adenocarcinoma. Among the 8 duodenal biopsies all showed features of chronic duodenitis. Conclusion: Biopsies helps in establishing a definite diagnosis of upper gastrointestinal lesions at an early stage thereby reducing the progression to invasive carcinoma